Peningkatan Partisipasi Politik Perempuan Bagi Kelompok PKK Dalam Pembangunan Desa di Desa Ledug Banyumas - Yunita Ratna Sari; Fitriatun Sururiyah; Khairunnisa Arifin; Zahrul Umam; Septi Wulandari; Tania Rahayu (STMIK Royal, 2026)
Abstract: Women's political participation is an important aspect in sustainable village development. However, the involvement of women including the PKK group in Ledug village, Kembaran sub-district, Banyumas faces obstacles ranging from a lack of understanding of political participation, village development, low education levels, time constraints, and traditional mindsets. This community service activity aims to increase the understanding, capacity, and political participation of women in the PKK group in Ledug village, Kembaran sub-district, especially in the village development process. The methods used include FGD, direct observation, counseling, and village forum simulations. The results of the activity show that the PKK Ledug group has a high motivation to be involved in village development but still faces obstacles such as limited information regarding village political mechanisms and lack of self-confidence. After the community service was implemented, the PKK Ledug group was able to convey aspirations in a more structured manner. The village forum simulation showed an increase in the activeness of the PKK Ledug group in discussions and submitting program proposals. This community service proves that political awareness can be an effective strategy to increase the contribution of the PKK Ledug group in village development. Keywords: women's political participation, village development Abstrak: Partisipasi politik perempuan merupakan aspek penting dalam pembangunan desa yang berkelanjutan. Namun, keterlibatan Perempuan termasuk kelompok PKK di desa Ledug kecamatan Kembaran, Banyumas menghadapi hambatan mulai kurangnya pemahaman tentang partisipasi politik, pembangunan desa, tingkat Pendidikan rendah, kendala waktu, pola pikir yang masih tradisional. Kegiatan pengabdian ini bertujuan untuk meningkatkan pemahaman, kapasitas, partisipasi politik perempuan kelompok PKK di desa Ledug, kecamatan Kembaran terutama proses Pembangunan desa. Metode yang digunakan meliputi FGD,observasi langsung,penyuluhan, simulasi forum desa. Hasil kegiatan menunjukkan kelompok PKK Ledug memiliki motivasi tinggi untuk terlibat dalam pembangunan desa tapi masih menghadapi kendala seperti keterbatasan informasi terkait mekanisme politik desa, minimnya kepercayaan diri.Setelah pengabdian dilaksanakan, kelompok PKK Ledug dapat menyampaikan aspirasi secara lebuh terstruktur.Simulasi forum desa memperlihatkan peningkatan keaktifan kelompok PKK Ledug dalam berdiskusi, mengajukan usulan program. Pengabdian ini membuktikan bahwa penyadaran politik dapat menjadi strategi efektif dapat meningkatkan konstribusi kelompok PKK Ledug dalam Pembangunan desa. Kata kunci: partisipasi politik perempuan, pembangunan desa